1996
DOI: 10.1016/0045-7930(95)00043-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and accuracy of time-accurate turbulent Navier-Stokes computations

Abstract: The accuracy and efficiency of two types of subiterations in both explicit and implicit Navier-Stokes codes are explored for unsteady laminar circular-cylinder flow and unsteady turbulent flow over an 18-percent-thick circular-arc (biconvex) airfoil. Grid and time-step studies are used to assess the numerical accuracy of the methods. Nonsubiterative time-stepping schemes and schemes with physical time subiterations are subject to time-step limitations in practice that are removed by pseudo time subiterations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 7 publications
3
60
0
1
Order By: Relevance
“…McDevitt et al 1976;Levy 1978;Marvin et al 1980). Since the frequency is greatly sensitive to the grid resolution and time step (Rumsey et al 1996), the agreement between the numerical result and the previous experimental data also verifies the reliability of the present simulation as described above. The location of shock wave motion along the surface is shown in figure 9(a), where t * represents the fractional cyclic time during one period, and t * = 0 is taken as the Mach number ahead of shock wave, where the solid line and the symbol respectively represent computational result and experimental data (Marvin et al 1980).…”
Section: Shock Wave Motionsupporting
confidence: 72%
See 1 more Smart Citation
“…McDevitt et al 1976;Levy 1978;Marvin et al 1980). Since the frequency is greatly sensitive to the grid resolution and time step (Rumsey et al 1996), the agreement between the numerical result and the previous experimental data also verifies the reliability of the present simulation as described above. The location of shock wave motion along the surface is shown in figure 9(a), where t * represents the fractional cyclic time during one period, and t * = 0 is taken as the Mach number ahead of shock wave, where the solid line and the symbol respectively represent computational result and experimental data (Marvin et al 1980).…”
Section: Shock Wave Motionsupporting
confidence: 72%
“…type A, B and C. Previous experimental studies of transonic flow over an 18 % thick circular-arc aerofoil at zero incidence have indicated that upstream-propagating shock waves occur alternately on the upper and lower surfaces for a certain range of the free-stream Mach number (McDevitt, Levy & Deiwert 1976;Levy 1978;McDevitt 1979;Marvin, Levy & Seegmiller 1980), which belongs to type C. Moreover, some numerical simulations have been performed using the time-dependent twodimensional Reynolds-averaged Navier-Stokes (RANS) equations with turbulence models (e.g. Marvin et al 1980;Rumsey et al 1996;Xiao, Tsai & Liu 2003). A zonal detached-eddy simulation (DES) method has also been used to predict the buffet phenomenon on a supercritical aerofoil (Deck 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When marching in pseudotime, this method permits the use of acceleration techniques such as local time step and multigrid to speed up the steady flows calculations. The application of dual-time stepping method of self-excited flow includes Rumsey et al 3 and Oliver et al 5 for the 18% circular-arc airfoil.…”
Section: Introductionmentioning
confidence: 99%
“…대류 플럭스항은 일반 좌표계에서 Roe FDS 기법을 사용하여 차분하였으며, 5차 MUSCL-TVD 기법 [13,14]을 이용하여 고차의 공 간차분 정확도를 유지하였다. 비정상 문제의 고 차 시간 정확도 해석 수행을 위하여 2차 정확도 의 Euler 후방 차분 및 이중 시간 부반복 (dual time sub-iteration)을 이용한 완전 내재적 기법을 물리적 시간에 적용하였다 [15].…”
Section: ⅲ 수치해석기법unclassified